Investment incentives of rent controls and gentrification: Evidence from German micro data - Vera Baye; Valeriya Dinger (Osnabrück University, Institute of Empirical Economic Research, 2023)
We empirically document that the effectiveness of the German rent control introduced in 2015 in achieving rental housing affordability is limited. Exploring the reasons for this limited effectiveness we focus on the impact of the rent control on the yield on rental housing investments proxied by rent-price ratios which we derive by matching micro-level quotes on similar objects offered for rent and for sale. Exploiting the temporal, regional, and objectspecific variation generated by the design of the rent control we identify a causal negative effect of the rent control on the yield of rental objects subject to the regulation. Further, we zoom into the spillovers across regulated objects and objects in the affected markets that were exempt from the regulation and find rising yields for the exempted objects, suggesting that the regulation contributed to gentrification via a shift of rental housing supply away from the regulated segment.
Keywords: R38; R31; E65; R21; R23; R10; 330; rent control; micro data; rent-price ratio; housing affordability; housing supply